2017
DOI: 10.1177/0884533616688432
|View full text |Cite
|
Sign up to set email alerts
|

From Evidence to Clinical Practice: Positive Effect of Implementing a Protein‐Enriched Hospital Menu in Conjunction With Individualized Dietary Counseling

Abstract: Providing a protein-enriched menu in conjunction with individualized dietary counseling significantly increased protein and energy intake in hospitalized patients at nutrition risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…We saw a clinically relevant increase in the intervention group of energy (1.5 MJ) and protein intake (14 gram). A statistical difference in protein and energy intake was found between the intervention and control groups in three comparable studies [13,20,21]. In our pilot study, the difference between protein and energy intake in the two groups was not statistically different but similar (or even higher) compared to the above mentioned three studies [13,20,21].…”
Section: Strengths and Limitationssupporting
confidence: 65%
“…We saw a clinically relevant increase in the intervention group of energy (1.5 MJ) and protein intake (14 gram). A statistical difference in protein and energy intake was found between the intervention and control groups in three comparable studies [13,20,21]. In our pilot study, the difference between protein and energy intake in the two groups was not statistically different but similar (or even higher) compared to the above mentioned three studies [13,20,21].…”
Section: Strengths and Limitationssupporting
confidence: 65%
“…Another study [12] investigated if a protein-enriched menu in conjunction with individualized dietary counseling by a clinical dietitian would increase energy and protein intake in hospitalized patients at nutrition risk as compared with providing the protein-enriched menu as a stand-alone intervention. This study concluded that providing a protein-enriched menu in conjunction with individualized dietary counseling by a dietitian significantly increased protein and energy intake in those hospitalized patients at nutrition risk.…”
Section: Discussionmentioning
confidence: 99%
“…Hospital malnutrition and decreased food intake present a significant burden for patient outcomes and healthcare costs globally (Agarwal et al, 2013;Corkins et al, 2014;Correia, Perman, & Waitzberg, 2017;Hiesmayr et al, 2009;Khalatbari-Soltani & Marques-Vidal, 2015). Increasing evidence of the prevalence and consequence of hospital malnutrition has prompted the investigation of a wide range of strategies to improve food intake, such as communal dining (Baptiste, Egan, & Dubouloz-Wilner, 2014), puree food moulds (Farrer, Olsen, Mousley, & Teo, 2016), protein-enriched hospital menu (Munk, Bruun, Nielsen, & Thomsen, 2017) and protected mealtimes (Porter, Haines, & Truby, 2017).…”
Section: Introductionmentioning
confidence: 99%